Flaky sputtered silicon MWCNTs core-shell structure as a freestanding binder-free electrode for lithium-ion battery - Seyed Ali Hoseini; Shams Mohajerzadeh; Zeinab Sanaee (Scientific Reports)
Abstract Core-shell silicon/multiwall carbon nanotubes are one of the most promising anode candidates for further improvement of lithium-ion batteries. Sufficient accommodation for massive volume expansion of silicon during the lithiation process and preventing pulverization and delamination with easy fabrication processes are still critical issues for practical applications. In this study, core-shell silicon/MWCNTs anode materials were synthesized using a facile and controllable PECVD technique to realize aligned MWCNTs followed by a silicon sputtering step. The use of the PECVD technique and the direct growth of multi-walled carbon nanotubes on the current collector creates a low tortuosity, flexible, and conductive scaffold, which, in addition to preventing CNT agglomeration, alleviates the pulverization and delamination of the silicon active material from the current collector, leading to the formation of an electrode with unique electrochemical performance. The CNT-Si core-shell electrode can achieve an excellent gravimetric specific capacity of 3250 mAh/g under a rate of C/5 and 99.8% capacity retention after more than 700 cycles. Electron microscopy revealed that the electrode structure has maintained its integrity and stability during long cycling (700 cycles and more). Apart from achieving high charging capacity, the use of such configuration leads to the formation of facile, inexpensive free-standing binder-free electrodes with no need to polymeric binders.